Comparison of the Urine Protein Examination Results Using the Dipstick Method and The Ewitz Method at Kabila Health Center - Sintia Ma'ruf; Astria Lolo; Adnan Engelene (LPPM Universitas Bina Mandiri Gorontalo, 2022)
This study aims to determine the differences in the results of urine protein examination in pregnant women using the dipstick method and the ewitz method at the Kabila Health Center, Bone Bolango district. The method used in this research is analytic observational by looking for the relationship between variables through an analysis of the data from observations in the laboratory or through observation of the analytical process. From the results of the study of 28 samples of pregnant women, it was found that there was no significant difference from the comparison of the results of urine protein examination using the dipstick method and the Ewitz method, where the p value was 1,000.